P–524 Is polycystic ovary syndrome really a risk factor for embryonic chromosomal aberrations? A multicenter retrospective cohort study. (6th August 2021) - Luo, L; Zhang, L; Wang, Q
Abstract: Study question: Does the rate of embryonic chromosomal aberrations increase in the setting of PCOS independent of maternal age and BMI? Summary answer: Controlling for maternal age and BMI, embryonic chromosomal aberration rate was not significantly different with controlled women undergoing preimplantation genetic testing for monogenic defects (PGT-M). What is known already: It has been reported that women with PCOS have higher risk of early spontaneous pregnancy loss, and it is well known that embryonic chromosomal abnormalities play an important role as a direct factor. However, whether PCOS women have increased risk of embryonic chromosomal aberrations remains inconclusive. Study design, size, duration: A multicenter retrospective cohort study was undertaken examining the incidence of chromosomal abnormalities in blastocysts using next-generation sequencing (NGS) for women undergoing PGT-M with and without PCOS (1398 PGT cycles, 5577 blastocysts) from 3 university-affiliated IVF centers between 2015 and 2019. Participants/materials, setting, methods: The blastocyst formation rate and the incidence of chromosomal abnormalities were compared between 163 PCOS women and 1235 non-PCOS women. Main results and the role of chance: Stratification analysis by maternal age with matched BMI showed no differences with regard to blastocyst formation rates for women with and without PCOS aged 20–29y (55.0% vs. 58.5%), 30–34y (54.7% vs. 58.9%) and >35y (56.7% vs. 52.4%), P > 0.05. The total embryonic chromosomal aberration rates for women aged 20–29y, 30–34y and >35y with and without PCOS were were also comparable, which were respectively 121/331 (36.4%) vs. 496/1209 (41.0%); 89/251 (35.5%) vs. 903/2175 (41.5%) and 72/130 (55.4%) vs. 789/1481 (53.3%), P > 0.05. Multivariate regression showed that controlling for maternal age and BMI, PCOS were not an independent risk factor for embryonic chromosomal abnormalities (OR = 0.89, 95% CI = 0.62 ∼ 1.35, P = 0.73). Limitations, reasons for caution: The study is mainly limited by its retrospective design and relatively smaller sample size for PCOS group which carries inherent potential for bias (i.e. misclassifification and errors due to inadequate clinical notes). Wider implications of the findings: Our results indicated that chromosomal abnormalities might not be the most important causal factor for the increased risk of early pregnancy loss for women with PCOS. By contrary, the non-chromosomal embryonic aberrations and/or maternal intrauterine factors could play more important role and needs to be clarifified Trial registration number: not applicable'